(untitled) (Eurasian Journal of Religious Studies, 2026)
The article is devoted to the analysis of the Islamic norms of halal animal slaughter in the Arabic-Kipchak text "Irshadul-muluk vas-salatin", a work of the Mamluk era. This work is main legal and theological source reflecting Hanafi view in the Turkic-Islamic intellectual tradition. Although it was studied from a linguistic and theological perspective, legal aspect of the text, especially on the issue of animal slaughter, has not been sufficiently examined. The article aims to study how animal slaughter is regulated in the "Kitab az-Zabaikh" part of the text and determine legal obligations of Muslims and people of the book in accordance with Islamic law. The study uses historical-genetic method, textual analysis and comparative legal methods, original Arabic text and its Kipchak translation are reviewed as separate but mutually supporting documents. Representatives of different Hanafi, Maliki and Shafii fiqh traditions were selected for systematic comparison of decisions. Three important legal criteria for animal slaughter are analyzed from the text. In addition, the article reveals that legal opinions in the Irshadul-muluk vas-salat comply with classical Hanafi jurisprudence and include madzhabar discussions. These findings indicate importance of the work in revealing practice of Islamic law in the Mamluk-Kipchak context. The scientific conclusions made in the study can be used as theoretical material in preparing Islamic studies discipline and as a practical guideline for Islamic clerics. Keywords: Kipchak, Hanafi, az-Zabih, Irshadul-Muluk was-Salatin, Madhhab